2003
DOI: 10.1002/ar.a.10082
|View full text |Cite
|
Sign up to set email alerts
|

Histological studies of bone formation during pedicle restoration and early antler regeneration in roe deer and fallow deer

Abstract: The purpose of the present study was to examine the process of bone formation in the regenerating cranial appendages of roe deer (Capreolus capreolus) and fallow deer (Dama dama) during the early postcasting period. After the antlers are cast, osteoclastic and osteoblastic activities lead to a smoothing of the pedicle's separation surface, a strengthening of the pedicle bone, and a partial restoration of the distal pedicle portion that was lost along with the cast antler. Initially, bone formation occurs by in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
96
1
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(105 citation statements)
references
References 29 publications
6
96
1
2
Order By: Relevance
“…However, it was later shown that antler regeneration can occur when the skin is not involved, leading to the formation of (stunted) 'skinless antlers' [55] . In contrast, our group suggested that the regenerating antler is formed by cells originating from the pedicle periosteum (PP) [40,41,43] . This view was initially based on the morphological analysis of double-head antlers, demonstrating that when the old antler is not cast, the regenerated antler develops as a periosteal exostosis from the distal pedicle [56] .…”
Section: Histo-and Morphogenesis Of the Regenerating Antlermentioning
confidence: 81%
See 4 more Smart Citations
“…However, it was later shown that antler regeneration can occur when the skin is not involved, leading to the formation of (stunted) 'skinless antlers' [55] . In contrast, our group suggested that the regenerating antler is formed by cells originating from the pedicle periosteum (PP) [40,41,43] . This view was initially based on the morphological analysis of double-head antlers, demonstrating that when the old antler is not cast, the regenerated antler develops as a periosteal exostosis from the distal pedicle [56] .…”
Section: Histo-and Morphogenesis Of the Regenerating Antlermentioning
confidence: 81%
“…During typical skin wound healing in adult mammals, the initially formed granulation tissue is transformed into the scar tissue [46,48] . A capillary-rich fibrocellular tissue resembling granulation tissue has also been reported to occur between the pedicle bone and the scab during casting wound healing [39,41,42] . The fate of this tissue has not been studied so far, but it is assumed that if a scar is formed during antler regeneration it is derived from it.…”
Section: Hard Antlers Antler Casting and Wound Healingmentioning
confidence: 99%
See 3 more Smart Citations